Dynamics in the history of religions between Asia and Europe : encounters, notions, and comparative perspectives - Krech, Volkhard.; Steinicke, Marion. (Dynamics in the History of Religions, 2012)
This first volume of the series "Dynamics in the History of Religions" reviews the opening conference of the \'Käte Hamburger Kolleg" at the Ruhr-University Bochum. The first section concentrates on the formation of what later come to be termed \'world religions\' through inter-religious contact, the second part focuses on the significance of interreligious contacts also during their expansive phase. Methodological problems of multi-perspective research and especially the lack of a general religious terminology are discussed in the third chapter, while the final papers outline various aspects of secularization and (re-)sacralisation in the age of globalisation as an effect of multicultural contacts in a world wide web of religious interferences.